Implementation of an Effective Strategy for Teaching Nontechnical Skills in the Operating Room: A Single-blinded Nonrandomized Trial. Issue 5 (May 2016) - Dedy, Nicolas J.; Fecso, Andras B.; Szasz, Peter; Bonrath, Esther M.; Grantcharov, Teodor P.
Abstract : Objective: To evaluate the effectiveness of debriefing and feedback on intraoperative nontechnical performance as an instructional strategy in surgical training. Background: Regulatory authorities for accreditation in North America have included nontechnical skills such as communication and teamwork in the competencies to be acquired by surgical residents before graduation. Concrete recommendations regarding the training and assessment of these competencies, however, are lacking. Methods: Nonrandomized, single-blinded study using an interrupted time-series design. Eleven senior surgical residents were observed during routine cases in the operating room (OR) at baseline and post-training. The Non-Technical Skills for Surgeons (NOTSS) rating system was used. Observers were trained in NOTSS and blinded to the study purpose. Independent of the blinded observations, a surgeon educator conducted intraoperative observations, which served as the basis for the structured debriefing and feedback intervention. The intervention was administered to participants after a set of (blinded) baseline observations had been completed. Primary outcome was nontechnical performance in the OR as measured by the NOTSS system. Secondary outcome was perceived utility as assessed by a post-training questionnaire. Results: Twelve senior trainees were recruited, 11 completed the study. Average NOTSS scores improved significantly from 3.2 (SD 0.37) at baseline to 3.5 (SD 0.43) post-training [ t (10) = −2.55, P = 0.29]. All participants felt the intervention was useful, and the majority thought that debriefing and feedback on nontechnical skills should be integrated in surgical training. Conclusions: Debriefing and feedback in the OR may represent an effective strategy to ensure development of nontechnical skills in competency-based education.